2023
DOI: 10.1007/s12035-023-03766-1
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Fingolimod in a Lafora Disease Mouse Model by Preventing Reactive Astrogliosis-Derived Neuroinflammation and Brain Infiltration of T-lymphocytes

Teresa Rubio,
Ángela Campos-Rodríguez,
Pascual Sanz

Abstract: Lafora disease (LD; OMIM#254780) is a rare, devastating, and fatal form of progressive myoclonus epilepsy that affects young adolescents and has no treatment yet. One of the hallmarks of the disease is the accumulation of aberrant poorly branched forms of glycogen (polyglucosans, PGs) in the brain and peripheral tissues. The current hypothesis is that this accumulation is causative of the pathophysiology of the disease. Another hallmark of LD is the presence of neuroinflammation. We have recently reported the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In addition, it has been reported that administration of DMF following status epilepticus increased Nrf2 activity, attenuated the status of epilepticus-induced neuronal cell death, and decreased seizure frequency and the total number of seizures compared to vehicle-treated animals [96]. However, when we used DMF in the Lafora disease mouse model, we observed only a minor effect; it was less effective in preventing neuroinflammation and T-lymphocyte infiltration [87].…”
Section: Dimethyl Fumaratementioning
confidence: 69%
See 1 more Smart Citation
“…In addition, it has been reported that administration of DMF following status epilepticus increased Nrf2 activity, attenuated the status of epilepticus-induced neuronal cell death, and decreased seizure frequency and the total number of seizures compared to vehicle-treated animals [96]. However, when we used DMF in the Lafora disease mouse model, we observed only a minor effect; it was less effective in preventing neuroinflammation and T-lymphocyte infiltration [87].…”
Section: Dimethyl Fumaratementioning
confidence: 69%
“…Recently, we have described the beneficial effects of FGD in a mouse model of Lafora disease, a particular type of progressive myoclonus epilepsy. In this model, FGD reduced reactive astrogliosisderived neuroinflammation and T-lymphocyte infiltration, which correlated with an improved behavioral performance among the treated animals [87]. However, in the case of the Rett syndrome, although the administration of fingolimod was safe in children with this disorder, it did not provide supportive evidence for an effect on clinical, laboratory, and imaging measures in these patients [88].…”
Section: Fingolimodmentioning
confidence: 82%